2014
DOI: 10.14202/vetworld.2014.980-985
|View full text |Cite
|
Sign up to set email alerts
|

Pathogens isolated from clinical mastitis in Murrah buffaloes and their antibiogram

Abstract: Aim: To determine the etiology of clinical mastitis in Murrah buffaloes and to develop an antibiogram of organisms isolated. Materials and Methods:A total of 564 quarter milk samples of 144 buffaloes suffering from clinical mastitis received in Veterinary College Central Laboratory were inoculated on blood agar, MacConkey's lactose agar and sabouraud dextrose agar. Bacteria isolated were characterized to the species level and subjected to in-vitro antimicrobial sensitivity testing.Results: Out of 564 quarters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 5 publications
(7 reference statements)
3
9
0
Order By: Relevance
“…Taken together, antibiogram profile of bacteria associated with bubaline SCM suggests high resistance to β-lactam antibiotics, corroborating several other studies on bovine and bubaline mastitis in India [ 34 , 81 – 84 ]. The high antibiotic resistance could be due to indiscriminate and injudicious use of antibiotics, about which there is no authentic data available even for cattle in India.…”
Section: Resultssupporting
confidence: 88%
“…Taken together, antibiogram profile of bacteria associated with bubaline SCM suggests high resistance to β-lactam antibiotics, corroborating several other studies on bovine and bubaline mastitis in India [ 34 , 81 – 84 ]. The high antibiotic resistance could be due to indiscriminate and injudicious use of antibiotics, about which there is no authentic data available even for cattle in India.…”
Section: Resultssupporting
confidence: 88%
“…Furthermore, a comprehensive examination of milk could offer important evidence concerning the nature of mastitis in dairy cattle and buffalo [ 35 ]. Bacterial species-wise prevalence estimates in this study were higher for S. aureus (38%) and St. dysgalactiae (15%), which were in agreement with a previous report [ 36 ]. Moreover, S. aureus in milk leads to food poisoning in human beings and is considered a public health concern.…”
Section: Discussionsupporting
confidence: 93%
“…The antibiogram profile of different bacterial isolates indicated that gentamycin, ciprofloxacin, enrofloxacin, tetracycline, Ampicilin and norfloxacin also proved as effective antimicrobials against S. aureus isolates in our study. Similar antibiogram patterns have been reported previously (Iqbal et al, 2004;Farooq et al, 2008;Charaya et al, 2014;Patnaik et al, 2014). This variability in sensitivity and resistance may be due to frequent and indiscriminate use of the antibiotics in different herds.…”
Section: Discussionsupporting
confidence: 89%